2019
DOI: 10.1029/2019sw002164
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Responses of Polar Ozone to Solar Proton Events in March 2012 by FengYun‐3 Satellite Observations

Abstract: In this work, we use observations by the Solar Backscatter Ultraviolet Sounder and Space Environment Monitor on FengYun-3 to analyze the polar ozone depletion during the solar proton events (SPEs), which occurred in early March 2012. The ozone distributions changed evidently with the increasing energetic proton flux (the particle energy is over 100 MeV) at the approximate altitude of 30 km. From the ozone profile relative changes, the short-term impacts of SPEs can be distinguished from the long-term effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The downward transport caused the upper stratospheric enhancements in NO x and then resulted in ozone reductions by photochemical reactions. Huang et al (2019) use observations by the Solar Backscatter Ultraviolet Sounder and Space Environment Monitor on FengYun-3 to study the polar ozone depletion at two different pressure levels in the stratosphere during the March 2012 SPEs. They found that the ozone depletion caused by the first SPE on March 7 was more noteworthy than the second one on March 13 at 30 km in both hemispheres due to the "harder" particle energy spectrum.…”
mentioning
confidence: 99%
“…The downward transport caused the upper stratospheric enhancements in NO x and then resulted in ozone reductions by photochemical reactions. Huang et al (2019) use observations by the Solar Backscatter Ultraviolet Sounder and Space Environment Monitor on FengYun-3 to study the polar ozone depletion at two different pressure levels in the stratosphere during the March 2012 SPEs. They found that the ozone depletion caused by the first SPE on March 7 was more noteworthy than the second one on March 13 at 30 km in both hemispheres due to the "harder" particle energy spectrum.…”
mentioning
confidence: 99%